Spanish validation of the short version of the racing and crowded thoughts questionnaire (RCTQ-13) (2024)
ABSTRACT: Background: The Racing and Crowded Thoughts Questionnaire (RCTQ-13) is the most widely used specific scale for the measurement of racing thoughts, but there is currently no Spanish version that allow the evaluation in Spanish-speaking patients. The objective of this study is to translate, adapt, and validate the RCTQ-13 in a Colombian population with affective disorders. Methods: The questionnaire was translated and back-translated, and corrections were implemented following a pilot test to improve comprehensibility. We included patients with Bipolar I Disorder and with Major depressive disorder seen in three centers in the city of Medellín, Colombia. We evaluate structural validity with confirmatory factor analysis, internal consistency, and test-retest reliability. Construct validity was also assessed with the comparison between euthymic, maniac, and depressive episodes and the correlation with worry, rumination, and mania scales. Responsiveness was measured 1 month after the first evaluation. Based on item response theory (IRT), we also estimated item difficulty, discrimination, and fit using a generalized partial credit model. Results: Two hundred fifty subjects were included. Confirmatory factor analysis revealed that the three-factor structure of the scale was appropriate. Internal consistency was adequate for the entire scale (Cronbach's alpha = 0.95, 95% CI: 0.94-0.96) and for each factor. Test-retest reliability was good (intraclass correlation coefficient = 0.82, 95%IC: 0.70-0.88). For construct validity, we observed differences between patients with different types of affective episodes, a moderate positive correlation with the Penn State Worry Scale (r = 0.55) and the Ruminative Response Scale (r = 0.42), and a low negative correlation with the Young Mania Rating Scale (r = - 0.10). Responsiveness was proved to be adequate. Under IRT, the response thresholds for the response options are organized for all items. The infit was adequate for all items and the outfit was acceptable. Conclusions: The Spanish version of the RCTQ-13 is a reliable, valid, and responsive scale and can be used for the clinical assessment of the construct of racing and crowded thoughts in patients with the spectrum of affective disorders in whom this experience can be expressed with different nuances. Further research is needed to expand the relationship with rumination and worry. Keywords: Anxiety; Bipolar disorder; Depressive disorder; Psychometrics; Psychopathology; Racing and crowded thoughts; Thinking.